Les marmites du Bayt al-mâl d’Alger. Charité, pouvoir et droits d’appartenance à l’époque ottomane - Isabelle Grangaud (L’Année du Maghreb)
This investigation was initiated by the astonishment (surprise) at the apparent incongruity of a large copper tableware estate preserved by an Algerian institution in charge of managing unclaimed property (the Bayt al-mâl).  Its results shed light on the ways in which the pots - and more broadly the utensils - used for communal meals were mobilised to form a society. We have highlighted the fact that, in addition to being able to form estates dedicated to a pious institution, the pots themselves could be these pious institutions (to which goods devoted to their cause could be devolved). Furthermore, the pious and charitable use that was made of them had in itself the force of law, it founded their legal status, as well as that of the social bodies that formed around these pious institutions. This enabled us to restore the civic dimension of the rights attached to these pots, whose collective use participated in the production of active social bodies. Indeed, these practices were the place and object of rallies, submissions and reciprocal obligations; they organised powers, affiliations, hierarchies and thresholds of insertion within these social bodies. In short, they were active modes of constructing the rights of belonging to political communities.